The Behavioral Regulation in Exercise Questionnaire (BREQ-3) Portuguese-Version: Evidence of Reliability, Validity and Invariance Across Gender - Cid, Luis (2018)
This study has as prime objective to analyze the psychometric properties of the Behavioral Regulation Exercise Questionnaire (BREQ-3) in a sample of Portuguese exercisers and invariance across gender. Two independent samples (448 calibration; 374 validation), aged between 16 and 78 years (M = 40.29; SD = 16.24), of both gender, (495 female; 327 male) were enrolled in this study. The results show that the original model (six factors; 24 items) did not fit to the data in a satisfactory way (χ 2 = 977.49; df = 237; B-S p < 0.001; SRMR = 0.07; NNFI = 0.80; CFI = 0.83; RMSEA = 0.08; 90% CI = 0.08–0.09). After removing six items (one for each factor), the model (six factors; 18 items) adjustment improved in a satisfactory way in both samples: calibration (χ 2 = 331.86; df = 120; B-S p < 0.001; SRMR = 0.06; NNFI = 0.91; CFI = 0.93; RMSEA = 0.06; 90% CI 0.06–0.07) and validation (χ 2 = 254.08; df = 120; B-S p < 0.001; SRMR = 0.04; NNFI = 0.93; CFI = 0.95; RMSEA = 0.06; 90% CI = 0.05–0.06). Results also showed model invariance across gender (1CFI ≤ 0.01). The Portuguese version of BREQ-3 (six factors; 18 items) is a valid and reliable measurement instrument to measure behavior regulation underlying self-determination theory in the exercise domain. However, the evidence also indicated that additional studies are needed to address the fragilities of the original model (six factors; 24 items).